Bringing back the saints: The contribution of the Roman edition of the Ruthenian liturgical books ("Recensio Ruthena", 1940--1952) to the commemoration of Slavic saints in the Ukrainian Catholic Church - Petrowycz, Michael (University of Ottawa (Canada), 2005)
The sanctorale of the Ruthenian (Kyivan) Catholic Church, as represented by the 1929 Lviv Liturgicon of Metropolitan Andrei Sheptytsy counted six saints of ancient Kyivan Rus' (tenth-eleventh centuries), three Lithuanian martyrs of the later medieval Kyivan Metropolitanate (fourteenth century), and Josaphat, martyred in 1623 for the cause of Union with Rome, canonized by Rome in 1867. In addition, there were Cyril and Methodius, and Parasceve (of Tarnovo, Bulgaria)---without the geographical identification. Previously there had also been authoritative Ruthenian Catholic calendars with only Josaphat. At the same time, the Ruthenian Orthodox calendar developed in the seventeenth century a Slavic sanctorale of many dozen, sometimes close to a hundred Slavic saints. In the course of a general revision of the Ruthenian liturgical books---the Recensio Ruthena (RR) editions (1940-1952), performed by the Congregation for the Eastern Church at the request of the Ruthenian bishops---the RR Commission admitted that from the historical perspective, and in the eyes of the Orthodox, this was a severe distortion of the Ruthenian sanctorale, and resolved to "restore to the Ruthenians their ancient saints." The present study investigates the deliberation process behind the RR Slavic sanctorale on two levels. First, it researches the motivations, the principles, and the sources of the work of the RR Commission on the basis of hitherto unpublished archival material---the two principal source documents of the Commission: the Osservatzioni, or preliminary commentary and suggestions prepared by Korolevskij, and the Minutes of the sessions of the RR Commission. Second, in order to fully appreciate the choices and the work of the RR Commission, the present study surveys both the Western theological discussion on the question of Eastern Slavic saints, and the development of diverse positions in the Ruthenian (and Russian) Catholic Church to these questions, whether in theological speculation or liturgical practice. (Abstract shortened by UMI.)
Keywords: Theology.